Dynamic passive insistence and maximal contraction: Flexibility influence on the karate split /Insistencia pasiva dinámica y contracción máxima: Influencia en la flexibilidad del Split en kárate - Edgar Jariff Oña Tacan; Daniel Nicolás Chamorro Werz; Enrique Chávez Cevallos (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
The physical capacity of flexibility is related to the possibilities possessed by a joint and muscle group in relation to a given range of motor movement. The capacity is usually determinant in various sports and of vital importance in karate athletes. Therefore, the objective of the research is to compare the dynamic passive insistence method (Mipd in Spanish) and the maximal contraction method (MCM in Spanish), assessing how they affect the flexibility of the coxofemoral joint in karate athletes, determining which method is more effective to increase flexibility in the frontal and lateral split. Experimental research of correlational type, studying 36 karate athletes (14-15 years old, male) divided into 18 subjects for each independent group (experimental and control). The subjects were intervened with an identical training model (five mesocycles), the difference being that the Mipd was applied to the control group and the MCM to the experimental group. For the experimental group, the lateral split test finally obtained a value of 6,6 cm, and the control group 2.72 cm. (+3.89 cm; p=0.002), while, for the experimental group in the frontal split test, a value of 7.72 cm was finally obtained, and the control group 1.06 cm (+6.66 cm; p=0.002). (+6.66 cm; p=0.000). The Mipd increases the level of flexibility, but the MCM is the ideal for an optimal development of coxofemoral flexibility in karate athletes, obtaining better progress in the opening of the legs in frontal and lateral split.